Brief notes about Europe and development - Proto Pisani, Andrea (2016)
The long-lasting European crisis induces the opponents of financial rigor to invoke growth policies. But an endless economic growth is definitely impossible. It is necessary to invest on the rediscovery of an authentic social humanism.